Sufficient and necessary conditions for the generalized distribution series to be in subclasses of univalent functions - Kota, W. Y.; El-Ashwah, R. M. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 517.5We establish a relationship between the subclasses of univalent functions and generalized distribution series. The main aim of our investigation is to obtain necessary and sufficient conditions for the generalized distribution series to belong to the classes ${\mathcal{TF}}(ρ,ϑ),$ $\mathcal{TH}(ρ,ϑ), \,\mathcal{TJ}(ρ,ϑ)$, and $\mathcal{TX}(ρ,ϑ)$. In addition, we obtain some particular cases of our main results.